Faktor Determinan Perilaku Image-based Sexual Abuse: Integrative Review - Viona Gunawan (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
As technology advances, technology-facilitated sexual crimes also emerge, one of which is Image-Based Sexual Abuse (IBSA) which is prevalent both internationally and in Indonesia. Various empirical studies have been conducted to examine the causative factors of IBSA perpetration and the results have been found to vary. Therefore, the authors made an integrative review study to map the determinants of IBSA behavior. The literature reviewed by the author was taken from two databases, namely Scopus and Clarivate Web of Science. Of the 996 identified literatures, 13 relevant literatures were obtained for further study. The determinant factors that were successfully mapped in this study were demographic, attitudinal, and experiential characteristics, dark personality traits, toxic online disinhibition, consumption of online pornography, and gender norms and homosocial interactions. Although the findings of previous studies varied widely, there were several inconsistent findings on the determinants. Therefore, future research can further examine this inconsistency.